Efektifitas pembelajaran mata kuliah akuntansi bisnis dengan pendekatan Construktivist Learning Design (CLD) berbantuan media E-learning - Iwan Koerniawan Siti Kholifah (Universitas PGRI Madiun, 2017)
Experience the ability of students using their knowledge have that has to review contruktivist the new knowledge is very media-influenced learning used one solution offered to review follow-up to these problems is a concept learning courses through construktivist business accounting teaching. singer study aims to determine the effectiveness of the learning review accounting subjects based business micruled assisted e-learning yang to review valid student learning. population research hearts hearts singer is whole semester students III study program computerized accounting STEKOM semarang. singer is an experimental research operates quasi experimental research (samsudi, 2006: 75) the review aims to improve student academic achievement on subjects accounting subjects who meet criteria for an effective business. tin research findings: (1) there is a positive effect of process skills against students' learning achievement is shown the effect of 55.6% contribution. (2) the learning achievement of the experimental classes more than learning achievement high grade control is shown with average - ratanya that is the average - average class experiment at 78 and the average - average grade control 65.7. so based on the findings of the research and discussion research above and learning business accounting subjects with construktivist aided teaching e-learning on business accounting subjects is effective.